Thermal insulation and energy performance's assessment of a mycelium-based composite wall for sustainable buildings - M. Fellah; S. Ouhaibi; N. Belouaggadia; K. Mansouri; H. Naji (Case Studies in Construction Materials, 2024)
Bio-composite insulation materials play a crucial role in reducing the environmental impact of buildings. This paper numerically investigates the eco-friendly application of mycelium in south-facing walls in Marrakech, Morocco, using 2D CFD simulations. In this context, the thermal efficiency of bio-sourced insulating materials was assessed and compared to that of conventional insulating materials. The study basically aims at the time lag and the decrement factor analysis to evaluate the dynamic thermal performance of a multilayer wall insulated with mycelium. A life cycle cost analysis (LCCA) is performed to establish the optimal thickness of the mycelium insulation, which was turned out to be 0.08 m. This optimization leads to a substantial improvement in energy efficiency, resulting in energy savings increasing by 87.4 % in winter and 55.9 % in summer. Besides, during the last 72 h of the simulation, the indoor surface temperature drops by approximately 4 °C on summer days and raises by approximately 1 °C on winter days. The thickness of mycelium insulation was found to have a significant impact on energy savings, increasing them from 56 % to 93 %, and representing nearly a 1.7-fold improvement. The study has also targeted annual CO2 emissions to reveal a potential reduction of around 72 % using optimal mycelium composite insulation. Finally, a comparative analysis with the guidelines of Moroccan thermal regulations was achieved. The obtained findings exhibit that the examined configuration excels in terms of thermal performance, economic feasibility, and environmental benefits.